A novel maraging stainless steel ultra-high-strengthened by multi-nanoprecipitations. (15th March 2023) - Wan, Jianquan; Ruan, Haihui; Ding, Zhiyi; Kong, Ling Bing
Abstract: A novel ultra-high strength maraging stainless steel with a chemical composition of Fe-11.5Cr-8.5Co-8.0Ni-5.0Mo-1.2Al-0.01C (in wt.%) has been developed. It utilizes a unique combination of nano scale intermetallic precipitates of Laves, β -NiAl, and sigma phases to achieve an ultra-high ultimate tensile strength up to 3.15 GPa, together with a balanced ductility and uniform elongation of about 2.74% and 2.05%, respectively. Maximizing the austenite content in the as-hot-rolled steel before cold-rolling and ageing treatments is essential to remove work-hardening behaviour and obtain an ultra-high strength without uniform elongation loss of the maraging steel. It is found that precipitation hardening sharply peaks at the ageing temperature of 525 °C for 3.5 h, which is mainly due to the peak strengthening effect of the net-like sigma phase through its transcrystalline fracture during tensile deformation. Graphical abstract: Image, graphical abstract